2018
DOI: 10.1111/jfbc.12623
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses pro-inflammatory adhesion response in Human Umbilical Vein Endothelial Cells

Abstract: Atherosclerosis, a progressive pathological disorder, is a leading cause of human morbidity and mortality worldwide. The expression of cell adhesion molecules by the endothelium and the attachment of monocytes to endothelium may play a pivotal role in the early atherogenic process. Curcumin, a polyphenol obtained from the root of turmeric, is the main component of curry powder. Previous studies indicated that curcumin exhibits a variety of pharmacological effects, including anti‐inflammatory, antitumor, antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Most notably, it prevents pathological VCAM-1 overexpression and leucocyte recruitment via the immunoblockade of antecedent NF-κB- and Toll-like receptor 4 –dependent pathways. 90–94 This atheroprotective potential has been corroborated in vivo with various animal models of experimental atherosclerosis. 95 , 96 , 140 In particular, Um et al 96 observed that curcumin treatment decreased mRNA and protein expression of ICAM-1, VCAM-1, P-selectin, and MCP-1 and resultant monocyte adhesion at atheroprone arterial regions in hypercholesterolaemic New Zealand white rabbits.…”
Section: Therapies That Suppress Vcam-1 Expression and Signallingmentioning
confidence: 83%
“…Most notably, it prevents pathological VCAM-1 overexpression and leucocyte recruitment via the immunoblockade of antecedent NF-κB- and Toll-like receptor 4 –dependent pathways. 90–94 This atheroprotective potential has been corroborated in vivo with various animal models of experimental atherosclerosis. 95 , 96 , 140 In particular, Um et al 96 observed that curcumin treatment decreased mRNA and protein expression of ICAM-1, VCAM-1, P-selectin, and MCP-1 and resultant monocyte adhesion at atheroprone arterial regions in hypercholesterolaemic New Zealand white rabbits.…”
Section: Therapies That Suppress Vcam-1 Expression and Signallingmentioning
confidence: 83%
“…We clearly observed that exposure of endothelial cells to Flonat Fast ® components reduced the expression of adhesion molecules involved in the attraction (MCP-1) and following firm adhesion of monocytes to endothelial cells (VCAM-1, and to a lesser extent ICAM-1) with a functional return expressed in a significant reduction of the number of monocytes adhering to the endothelium. Modulation of endothelial adhesion molecule expression has already been studied with success in the presence of E [ 71 ], BS [ 72 ], and C [ 73 ], but, to our knowledge, no literature reports for B and HP. Our data fully support this evidence, as we did not observe any modulatory effect of B and HP on their own.…”
Section: Discussionmentioning
confidence: 99%